2013
DOI: 10.1667/rr3182.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cell Killing and Autosomal Mutation in Mouse Kidney Epithelium Exposed to 1 GeV ProtonsIn VitroorIn Vivo

Abstract: Human exposure to high-energy protons occurs in space flight scenarios or, where necessary, during radiotherapy for cancer or benign conditions. However, few studies have assessed the mutagenic effectiveness of high-energy protons, which may contribute to cancer risk. Mutations cause cancer and most cancer-associated mutations occur at autosomal loci. This study addresses the cytotoxic and mutagenic effects of 1 GeV protons in mouse kidney epithelium. Mutant fractions were measured for an endogenous autosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
6
11
0
Order By: Relevance
“…Si ions were also quite mutagenic with evidence for a linear dose–response for Aprt mutations in kidney cells exposed in vitro or in kidneys harvested from mice irradiated several months earlier. These results are consistent with the linear dose–response data obtained previously for Aprt mutation induction following Fe ion exposure in vitro or in vivo , but the results for Si ions differ from the curvilinear dose–response data we recently published following similar exposures to energetic protons [ 1, 2]. Our most recent studies examined the molecular characteristics of Si ion-induced Aprt mutants following in vitro exposure.…”
supporting
confidence: 91%
“…Si ions were also quite mutagenic with evidence for a linear dose–response for Aprt mutations in kidney cells exposed in vitro or in kidneys harvested from mice irradiated several months earlier. These results are consistent with the linear dose–response data obtained previously for Aprt mutation induction following Fe ion exposure in vitro or in vivo , but the results for Si ions differ from the curvilinear dose–response data we recently published following similar exposures to energetic protons [ 1, 2]. Our most recent studies examined the molecular characteristics of Si ion-induced Aprt mutants following in vitro exposure.…”
supporting
confidence: 91%
“…In contrast, although increases in Aprt mutant frequencies were observed at 0.5 and 1.0 Gy protons (~1.4 fold in both cases), these increases were not statistically significant (p = 0.279 and 0.109, respectively) (Table 1). Adding these data to mutant frequency data obtained at higher doses in a prior study (3.0, 4.0, and 5.0 Gy) [13] confirmed that the proton dose response is curvilinear, with little or no change at the lower doses and a doubling dose estimated at approximately 2–2.5 Gy (Fig 1). The adjusted R-squared value for all proton mutant frequencies is 0.93.…”
Section: Resultssupporting
confidence: 60%
“…Results for mutant frequencies and toxicity are presented in Table 1 and Figs 1 (mutant frequencies) and 2 (toxicity). The Table and Figures are supplemented with data from a prior study using doses of 3, 4, or 5 Gy protons [13]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be useful if GCR simulation addresses both cell and animal studies and it may be feasible to design some experiments that allow direct comparison of the in vitro and in vivo (Kronenberg et al, 2009, 2013) systems. In some cases, the less expensive cell culture experiments may mimic what happens in the body.…”
Section: Issues Common To Both Gcr Simulation and Single Beam Expementioning
confidence: 99%